English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

if v/a=e/b=f/c

why is it true these three things are equal to (v-e+f)/(a+b+c)?

ie. how do u get from v/a=e/b=f/c to
v/a=e/b=f/c=(v-e+f)/(a+b+c)

2006-12-07 07:23:04 · 3 answers · asked by Milo 4 in Science & Mathematics Mathematics

sorry it should be (v-e+f)/(a-b+c) i think

so there is a minus between a and b

2006-12-07 07:30:45 · update #1

3 answers

Thats not true.. (eg take the fractions to be 1/2, 2/4, 3/6. Then you get 2/12, which isn't 1/2).

However, it is true for (v+e+f)/(a+b+c).

Just let x = v/a = e/b = f/c. Then v = ax, e = bx, f = cx, so (v+e+f)/(a+b+c) = (ax+bx+cx)/(a+b+c) = x.

Edit - and that works just the same for (v-e+f)/(a-b+c): you have (ax - bx + cx)/(a-b+c) = x(a-b+c)/(a-b+c) = x.

2006-12-07 07:31:05 · answer #1 · answered by stephen m 4 · 1 0

i don't think the last equation is valid

(try plugging in arbitrary numbers, and then you'll see what i'm saying)

2006-12-07 07:29:25 · answer #2 · answered by orca1006 2 · 0 0

it is a property of ratios and proportions

2006-12-07 07:27:04 · answer #3 · answered by raj 7 · 0 1

fedest.com, questions and answers